2018
DOI: 10.1093/ehjci/jey047
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial fibrosis as an early feature in phospholamban p.Arg14del mutation carriers: phenotypic insights from cardiovascular magnetic resonance imaging

Abstract: LV myocardial fibrosis is present in many PLN p.Arg14del mutation carriers, and who still have a preserved LVEF. It is seen predominantly in the LV inferolateral wall and corresponds with electrocardiographic repolarization abnormalities. Although preliminary, myocardial fibrosis was found to be independently associated with VA. Our findings support the use of CMR with LGE early in the diagnostic work-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 29 publications
1
57
0
Order By: Relevance
“…Interestingly, this pathogenic variant was described as a founder mutation in the Netherlands, and was identified in ±14% of Dutch patients with dilated cardiomyopathy (DCM) or arrhythmogenic right ventricular cardiomyopathy (ARVC), which translates into thousands of carriers 9 . PLN-R14del carriers have a high risk of developing malignant ventricular arrhythmias (VAs) and HF, and are often diagnosed with DCM or ARVC, which, given the presence of biventricular abnormalities, is better referred to as arrhythmogenic cardiomyopathy (ACM) 3,[9][10][11] . The phenotype is typically characterized by ECG abnormalities, including low QRS-potentials and inverted T-waves in precordial leads, myocardial fibrosis and fibrofatty replacement, and, ultimately, severe biventricular dysfunction and HF 3,9,10 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this pathogenic variant was described as a founder mutation in the Netherlands, and was identified in ±14% of Dutch patients with dilated cardiomyopathy (DCM) or arrhythmogenic right ventricular cardiomyopathy (ARVC), which translates into thousands of carriers 9 . PLN-R14del carriers have a high risk of developing malignant ventricular arrhythmias (VAs) and HF, and are often diagnosed with DCM or ARVC, which, given the presence of biventricular abnormalities, is better referred to as arrhythmogenic cardiomyopathy (ACM) 3,[9][10][11] . The phenotype is typically characterized by ECG abnormalities, including low QRS-potentials and inverted T-waves in precordial leads, myocardial fibrosis and fibrofatty replacement, and, ultimately, severe biventricular dysfunction and HF 3,9,10 .…”
mentioning
confidence: 99%
“…In 2021 we expect the results of the PHOspholamban RElated CArdiomyopathy STudy -Intervention (i-PHORECAST; ClinicalTrials.gov NCT01857856). As myocardial fibrosis is considered to be an early disease manifestation in this cardiomyopathy 7,11,14 , the i-PHORECAST study aims to test the efficacy of the mineralocorticoid receptor antagonist (MRA) eplerenone, which has been shown to exert anti-fibrotic effects 15 , in reducing disease progression or postponing onset of overt disease in asymptomatic mutation carriers.…”
mentioning
confidence: 99%
“…The hearts showed biventricular presence of fibrofatty replacement and interstitial fibrosis, in line with our previous pathological [8][9][10] and cardiac magnetic resonance imaging findings. 20 Sepehrkhouy et al recently showed this fibrosis pattern to be distinctive for PLN p.Arg14del cardiomyopathy in comparison with other hereditary cardiomyopathies. 10 Clinically, the majority of patients (63%) in our cohort fulfilled criteria for both ARVC and DCM.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have demonstrated that phospholamban mutation carriers with T‑wave inversion were more likely to have left ventricular late gadolinium enhancement on cardiac MRI, compared to those without T‑wave inversion. In our cohort, we demonstrated a strong association between T‑wave inversion and LV dysfunction among mutation carriers [ 11 ]. Furthermore, fibrosis and fatty changes among phospholamban carriers may also occur in a distinct pattern compared to other forms of hereditary cardiomyopathies [ 12 ].…”
Section: Discussionmentioning
confidence: 99%